Dietary characterization of the endangered salt marsh harvest mouse and sympatric rodents using DNA metabarcoding. Issue 7 (17th July 2022) - Aylward, Cody M.; Statham, Mark J.; Barthman‐Thompson, Laureen; Kelt, Douglas A.; Sacks, Benjamin N.
Abstract: The salt marsh harvest mouse ( Reithrodontomys raviventris ; RERA) is an endangered species endemic to the coastal wetlands of the San Francisco Estuary, California. RERA are specialized to saline coastal wetlands, and their historical range has been severely impacted by landscape conversion and the introduction of non‐native plant and rodent species. A better understanding of their diet is needed to assess habitat quality, particularly in relation to potential competitors. We investigated three questions using DNA metabarcoding with ITS2 and trnL markers: (1) Do RERA specialize on the native plant, pickleweed ( Salicornia pacifica ), (2) Do RERA consume non‐native plants, and (3) What is the dietary niche breadth and overlap with three sympatric native and non‐native rodents? RERA diet was dominated by two plants, native Salicornia and non‐native salt bush ( Atriplex spp . ), but included 48 plant genera. RERA diet breadth was narrowest in fall, when they consumed the highest frequencies of Salicornia and Atriplex, and broadest in spring, when the frequencies of these two plants were lowest. Diet breadth was slightly lower for RERA than for co‐occurring species in pairwise comparisons. All four species consumed similarly high frequencies of wetland plants, but RERA consumed fewer grasses and upland plants, suggesting that it may be less suited to fragmented habitat than sympatric rodents. Diet overlap was lowest between RERA and the native California vole ( Microtis californicus ). In contrast, RERA diet overlapped substantially with the native western harvest mouse ( R. megalotis ) and non‐native house mouse ( Mus musculus ), suggesting potential for competition if these species become sufficiently abundant. Abstract : We used DNA metabarcoding to characterize the diet of the endangered salt marsh harvest mouse ( Reithrodontomys raviventris ) and three sympatric rodents. We found that salt marsh harvest mice had a broad diet but appeared to prefer pickleweed ( Salicornia pacifica ) and fat‐hen ( Atriplex prostrata ). Salt marsh harvest mouse diet strongly overlapped sympatric generalist rodents, but was more restricted, suggesting that dietary competition and habitat fragmentation are potential threats to salt marsh harvest mice.